Common Mental Disorder and early interruption of exclusive maternal breastfeeding in Quilombola women: a population-based study - Vanessa Gabrielle dos Santos Araújo; Tamara Rodrigues dos Santos; Ana Carolina Santana Vieira; Monica Lopes de Assunção; Haroldo da Silva Ferreira (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to investigate the prevalence of exclusive maternal breastfeeding (EMBF) and evaluate whether common mental disorder (CMD) and other predictors promote its early interruption (EI-EMBF4). Methods: a cross-sectional study involving all children <24 months (n=252) residing in 50% (n=34) of the Quilombola communities in Alagoas. The EI-EMBF4 was established when EMBF was ≤4 months. The Self-Reporting Questionnaire was used to identify the occurrence of CMD. Other predictors were obtained through interviews. The measure of association was the prevalence ratio calculated by the Poisson regression, following a hierarchical theoretical model. The prevalence of EMBF for 4 and 6 months, and its median duration (survival analysis) were calculated. Results: the prevalence of EI-EMBF4 and CMD was 57.6% and 42.9%, respectively. The risk factors independently associated with EI-EMBF4 were: living in a mud house, maternal age ≤18 years, low birth weight and the use of a pacifier or baby bottle. There was no association with CMD. The prevalence of EMBF for four and six months was 42.4% and 25.4%, respectively, and the median duration was 106 days. Conclusion: EMBF indicators are below the established recommendations, justifying the implementation of measures that prioritize women subjected to risk factors identified here. CMD is not configured among these.